The Effect of Drill Practice Method on Battom Passing Ability in Volleyball Game of Extracurricular Participants of Stagte High School 1 Jarai, Lathat Regency - Muhammad Firza Eldani; M. Haris Satria; Noviria Sukmawati; Dewi Septaliza (Universitas Pendidikan Ganesha, 2024)
The purpose of this study is to determine the influence of the drill practice method on the ability to pass down in volleyball games of extracurricular participants of State High School 1 Jarai. The method in this study is quantitative using pre-experimental research. The instrument in this study is using the Braddy Volleyball Test. The sample in this study is 34 volleyball players from SMA Negeri 1 Jarai Class X. The sample in this study was selected using the total sampling technique. The data analysis technique uses a paired sample t test. From the results of the study, it can be concluded that there is an effect of drill method practice on the ability to pass down in volleyball games of extracurricular participants of State High School 1 Jarai Lahat Regency, this is because the calculated t value is 7.840 > the table is 2.036 and the significance value is 0.000 < 0.05. The percentage of the influence of drill method practice on the ability to pass down in volleyball games of extracurricular participants of State High School 1 Jarai Lahat Regency was 80.03% while the remaining 19.97% was influenced by other volleyball practice program variables that were not studied. For the Physical Education Teacher of State High School 1 Jarai Lahat Regency, due to the limited time of extracurricular participants, it is expected to be able to apply effective learning methods by designing a good form of learning in order to obtain optimal learning outcomes, one of which is by playing.